2021
DOI: 10.3390/metabo11050280
|View full text |Cite
|
Sign up to set email alerts
|

Leafy Stems of Phagnalon saxatile subsp. saxatile from Algeriaas a Source of Chlorogenic Acids and Flavonoids with Antioxidant Activity: Characterization and Quantification Using UPLC-DAD-ESI-MSn

Abstract: Phagnalon saxatile subsp. saxatile is a wild species widespread in Algeria which is utilized for medicinal purposes as analgesic and anticholesterolemic. However, information is still scarce regarding its phytochemical content. The objective of this study was to identify and quantify the phenolic compounds from different extracts of its leafy stems. For this purpose, the effects of four extracting solvents were investigated on the content of phenolic compounds and the antioxidant activity of this plant. The ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The extraction method involved the use of a Soxhlet apparatus, with methanol serving as a solvent, following the protocol described by Haddouchi et al [13] . Through this method, the solvent was completely evaporated, resulting in a methanol extract with an extraction yield up to 19.1 %.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extraction method involved the use of a Soxhlet apparatus, with methanol serving as a solvent, following the protocol described by Haddouchi et al [13] . Through this method, the solvent was completely evaporated, resulting in a methanol extract with an extraction yield up to 19.1 %.…”
Section: Methodsmentioning
confidence: 99%
“…The extraction method involved the use of a Soxhlet apparatus, with methanol serving as a solvent, following the protocol described by Haddouchi et al [13] Through this method, the solvent was completely evaporated, resulting in a methanol extract with an extraction yield up to 19.1 %. The specimen was meticulously gathered and preserved at 4 °C for subsequent examination and possible application in scientific research.…”
Section: Experimental Sample Collection and Extractionmentioning
confidence: 99%
“…These compounds are mostly found in fruits, cereals, vegetables, and beverages [ 14 , 15 ]. Phenolic acids, flavonoids, stilbenes, and lignans are among the main polyphenolic categories that exert antioxidant activity by scavenging free radicals and disrupting oxidative reactions [ 14 , 16 ]. Studies with diets rich in these polyphenolic compounds have been found to shield from oxidative stress and protect from a wide range of diseases such as osteoporosis, cancer, diabetes, cardiovascular, and neurodegenerative diseases [ 6 , 17 , 18 , 19 , 20 , 21 ]; these studies add a translational value to the in vitro studies that have investigated the antioxidant potential of new compounds from natural products or foods.…”
Section: Introductionmentioning
confidence: 99%